PENDUDUK, OTONOMI KHUSUS, DAN FENOMENA KONFLIK DI TANAH PAPUA - La Pona (Jurnal Kependudukan Indonesia, 2008)
The dynamic of population in Papua region dominant influenced by migration process, and create plural societies in urban and rural area. The dynamic of population produce the specific of social structure, social stratification, and social networking in this society which are multi race, multi ethnic, multi cultural, multi religion, and multi region. This condition must be careful, because of having posit if and negatif inpact in development process. That condition could make the social strained condition, weakness capacity of social receive, and conflict situation which must be understood. The social-political conditions influenced the conflict construction in this plural society. To Create the awarness, common will, political will, social networking, and cross cutting affiliation in this plural society are very important to avoid or minimize the social strained, controversy, dispute, contradiction, opposition, resistance, or conflict in this plural society.Keyword: Population, Plural, Politic, Conflict